IMPLEMENTASI DIGITAL LEARNING DALAM PELAKSANAAN DIKLAT KARYAWAN TELKOM CORPORATE UNIVERSITY:Studi Deskriptif di Telkom Corporate University Bandung - Anjani, Widi (2017)
Penelitianiniterkaitdenganimplementasidigital learning dalampelaksanaandiklatkaryawanTelkom Corporate University Bandung. PenelitianinibertujuanuntukmendeskripsikanbagaimanaimplementasiDigital Learning dalampelaksanaandiklatkaryawanTelkom Corporate University.Tujuanpenelitianiniuntukmendeskripsikan: (1) PerencanaanDigital Learning dalampelaksanaandiklatkaryawanTelkom Corporate University, (2) PelaksanaanDigital Learning dalampelaksanaandiklatkaryawanTelkom Corporate University, (3) KetercapaiankompetensipesertadiklatsetelahmelaksanakanDigital Learning Telkom Corporate University, (4) ResponpesertadiklatterhadapDigital Learning dalampelaksanaandiklatkaryawanTelkom Corporate University, dan (5) FaktorpendukungdanpenghambatdalampengimplementasianDigital Learning dalampelaksanaandiklatkaryawanTelkom Corporate University.Penelitianinimenggunakanmetodedeskriptifjenisstudikasusdenganpendekatankuantitatif. Teknikpengumpulan data berupapedomanangket, wawancara, danstudidokumentasi. Sampel yang digunakanadalahtiga orang manager unit kerjaKnowledge Management and Case Study Telkom Corporate University dan 44 orang pesertadenganteknikpengambilanpurposive sampling. Berdasarkanhasilpenelitian, implementasidigital learning dalampelaksanaandiklatkaryawanTelkom Corporate University telahberhasilmemanfaatkanteknologidalammelaksanakandiklatbagikaryawan, sehinggamembuatpembelajaranlebihefisien, modern, danmenyenangkan, sertamemberikandampakpositifbagikaryawankarenadenganadanyadigital learning dapatmemfasilitasikaryawan agar dapatmelakukanpembelajaran any how, any where, any who, and any time melalui model integrated learning cycle yang diterapkannya, Kata Kunci :Implementasi, Digital Learning, E-learning,Diklat, This research discusses about the implementation of digital learning on training and education program for the employees of Telkom Corporate University Bandung. This research aims to describe how is the implementation of digital learning on training and education program for the employees of Telkom Corporate University Bandung. Moreover, the aims of this research is to describe: (1) The planning of digital learning on training and education program for the employees of Telkom Corporate University, (2) The implementation of Digital Learning on training and education program for employees of Telkom Corporate University, (3) The achievement of participants' competence after doing Digital Learning Telkom Corporate University, (4) The response of participants toward Digital Learning on training and education program for the employees of Telkom Corporate University, and (5) The supporting and inhibiting factors in the implementation of Digital Learning on training and education program for the employees of Telkom Corporate University. This research uses descriptive quantitative method. Furthermore, the data are collected from questionnaire, interview, and document analysis. The sample used in this research is 3 managers in Department of Knowledge Management and Case Study Telkom Corporate University and 44 participants. They are chosen by using purposive sampling technique. The result shows that the implementation of digital learning on training and education program for the employees of Telkom Corporate University has succeeded to utilize technology; therefore, the learning is more efficient, modern, and fun. Also, it gives positive impact to the employees since the existence of digital learning is able to facilitate them to do any how, any where, any who, and any timelearning through integrated learning cycle which is applied. Keywords: Implementation, Digital Learning, E-learning, Training and Education Program